Experimental and numerical studies of the shear resistance capacities of interlocking blocks. (December 2021) - Shi, Tingwei; Zhang, Xihong; Hao, Hong; Xie, Guanyu
Abstract: Interlocking bricks could improve construction efficiency, reduce labour cost, and provide better mechanical performance for masonry structures. Nevertheless, the shear properties of mortar-less interlocking bricks have not been systematically investigated which may impede their wide applications. In this study, the shear performance of a new type of interlocking brick is investigated in detail. Laboratory shear test is firstly conducted to study the damage and shear capacity of mortar-less (dry-stacked) interlocking bricks. Numerical model is then generated with consideration of contact imperfection and validated with test results. Intensive parametric studies are conducted to quantify the influences of material strength, axial pre-compression force, friction coefficients, and contact imperfection at brick interfaces on the shear response of interlocking prisms. The accuracy of existing methods for predicting the shear capacities of shear key by design standard and empirical formula are evaluated. Based on the numerical and laboratory results, an empirical design formula is proposed to predict the shear capacity of the interlocking brick. Highlights: Tests are conducted on the shear capacity of interlocking brick. Factors influencing the shear capacity are summarised. A formula is proposed for the interlocking brick shear strength prediction.